GENIUS LOCI IN WOT BATU - Khairi Ilman Chandra ; Caecilia S. Wijayaputri (Riset Arsitektur (RISA), 2019)
Abstract- In a modern environment, the existence of genius loci is starting to become rare. Places seem to lose their defining characteristics and this diminishes people’s experience with them. In 2015, Sunaryo succeeded in building Wot Batu as a place that can exemplify a “man-made place” created in “modern” times that can showcase the existence of a genius loci. Therefore, this research discusses the factors that contribute to the emergence of genius loci and how it emerged in Wot Batu. This research employs a descriptive-qualitative approach. The researcher analyzes theories that are related to definitions of, factors that constitute place, and types of genius loci, which are then utilized to provide an observation of the object. The data that is gathered consist of organizations of spatial structure and articulation of concrete properties. In addition, the researcher also interviewed Sunaryo Sutono about the background of Wot Batu.  The researcher identifies and classifies said data in a table of factors that constitute place which are then summarized to serve as a basis for explaining the genius loci that is established in Wot Batu. In Wot Batu, the creator’s strong intent to express spiritual meanings is accomplished in a specific way. The complexity of that spiritual understanding is manifested in its spatial structures and concrete properties that are impressively detailed. The ideas and personal life experiences that were once only found in Sunaryo Sutono’s mind are brought into the world as a very specific place, and those things eventually coalesce into a totality and form genius loci that is meaningful to its user.  Key Words: genius loci, Wot Batu, Sunaryo, Ciburial Bandung